Application of CORE Learning Model with Molymod-Assisted on Hydrocarbon Material to Improve the Students’ Learning Outcomes - Gleryl F. Novemly; Mery Napitupulu; Ijirana Ijirana (Jurnal Akademika Kimia, 2022)
This study aimed to describe the improvement of learning outcomes by applying the learning model of Connecting, Organizing, Reflecting, Extending (CORE) with molymod-assisted hydrocarbon material of class X students of SMA Labschool UNTAD Palu. This type of research was experimental designs with one group pretest-posttest design. This study used 2 classes, namely class XA as replication class 1 (n = 26) and class XB as replication class 2 (n = 27). The students' learning outcomes were affective, psychomotor, and cognitive aspects. In replication class 1, the value of student learning outcomes was 71.37, while in replication class 2 was 66.00. The data analysis results showed increased student learning outcomes after using the Molymod-assisted CORE learning model in both classes. So it can be concluded that applying the Molymod-assisted CORE learning model on hydrocarbon materials can improve student learning outcomes for class X SMA LABSCHOOL UNTAD Palu.